Invariance on a reading comprehension test in European Portuguese: a differential item functioning analysis between students from rural and urban areas - Cadime, Irene Maria Dias (2014)
The aim of this study was to determine whether the items from a reading comprehension test in European Portuguese function differently across students from rural and urban areas, which biases the test validity and the equity in assessment. The sample was composed of 653 students from second, third and fourth grades. The presence of differential item functioning (DIF) was analysed using logistic regression and the Mantel–Haenszel procedure. Although 17 items were flagged with DIF, only five items showed non-negligible DIF in all effect-size measures. The evidence of invariance across students with rural or urban backgrounds for most of the items supports the validity of the test though the five identified items should be further investigated.